2016
DOI: 10.1007/978-981-10-1082-8_9
|View full text |Cite
|
Sign up to set email alerts
|

The Hardness Variation Due to Secondary Heating in Friction Stir Welding of Small Diameter Aluminium Alloy 6063 Pipe

Abstract: Friction stir welding (FSW) is a solid state joining process which utilizes the frictional heat of a high speed rotating tool to soften the adjoining sections and stirred/joined them together as one part without filler. In the FSW of pipe joining, a tool rotating at high speeds will start and stop at the same point in order to complete full weld cycle. The FSW of a small diameter pipe can cause secondary heating to occur at the start and stop point. Several pipe samples of 89 mm outside the diameter were prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…There are relatively few attempts made to study the out of position FSW of ferrous and non-ferrous materials [9][10][11]. For example, Ismail et al [12,13] studied the effect of welding parameters on the tensile strength of joint produced by the butt FSW on 89 mm AA6063-T6 pipe with a thickness of 5 mm. They reported that the increase in rotation and travel speeds increases the tensile strength and then starts decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…There are relatively few attempts made to study the out of position FSW of ferrous and non-ferrous materials [9][10][11]. For example, Ismail et al [12,13] studied the effect of welding parameters on the tensile strength of joint produced by the butt FSW on 89 mm AA6063-T6 pipe with a thickness of 5 mm. They reported that the increase in rotation and travel speeds increases the tensile strength and then starts decreasing.…”
Section: Introductionmentioning
confidence: 99%
“…Linear FSW performance does not depend upon many adaptations other than effective clamping; however, when using a standard milling machine for an OFSW procedure, such as the joining of tubes or cylindrical workpieces, some apparatus is required to be incorporated into the milling machine not only as a holding mechanism for the workpieces to be joined, supporting all the forces and torques inherent to FSW, but also to be responsible for the rotation of the workpiece at a constant speed (travel speed) beneath a rotating stationary tool of the milling machine. This apparatus is referred to as the "Orbital Clamping Unit" [58]. When designing this clamping device, several characteristics of the process, such as torque, spindle speed, plunge load, transverse load, and slide force, should be evaluated and quantified, as it must support all the forces inherent to the process.…”
Section: Equipment Requirements For Orbital Fswmentioning
confidence: 99%
“…Ismail et al [39] conducted a study in order to acquire the characteristic temperature curves during the plunging stage (before the travel of the tool) of OFSW in an AA6063-T6 tubular specimen of 89 mm outside diameter and a thickness of 5 mm, carrying out a comparison between different tool rotational speeds from 900 to 1700 rpm. They maintained the other process parameters, such as a plunge depth of 4 mm, a plunge rate of 10 mm/min, an offset of 6 mm, and a dwell time of 30 s, and used K-type thermocouples to measure the temperature and position them as depicted in Figure 22.…”
Section: Temperature Measurement and Profilesmentioning
confidence: 99%
“…At the point when the shoulder comes into contact with the outside of plates, the temperature increases because of the heat created, and the pin of the shoulder blends in the joining surface permitting the streaming of the material rear of the pin. As the drill passes, the metal cools and a prepared zone is delivered [3].…”
Section: Introduction 1friction Stir Weldingmentioning
confidence: 99%